2006
DOI: 10.1097/01.hjh.0000242400.37967.54
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of physical activity leads to a greater blood pressure reduction than a single continuous session, in prehypertension

Abstract: The accumulation of physical activity appears to be more effective than a single continuous session in the management of prehypertension. Sympathetic modulation was associated with reduced blood pressure after each session.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
80
4
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 27 publications
6
80
4
9
Order By: Relevance
“…The finding that fractionized exercise was superior to a traditional continuous session of exercise for lowering SBP in afternoon and early evening hours is in agreement with Park et al 4 who observed a more prolonged reduction in BP after fractionized exercise compared with a single continuous exercise session in prehypertensives. Our results extend these findings to normotensives and suggest that BP reductions can be achieved by evenly distributing 10-min exercise sessions throughout the day as compared with multiple 10-min exercise sessions primarily in the morning.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…The finding that fractionized exercise was superior to a traditional continuous session of exercise for lowering SBP in afternoon and early evening hours is in agreement with Park et al 4 who observed a more prolonged reduction in BP after fractionized exercise compared with a single continuous exercise session in prehypertensives. Our results extend these findings to normotensives and suggest that BP reductions can be achieved by evenly distributing 10-min exercise sessions throughout the day as compared with multiple 10-min exercise sessions primarily in the morning.…”
supporting
confidence: 90%
“…2 PEH has been reported to be B7-14 mm Hg, can occur within 5 min after exercise, and may persist for up to 22 h. 2,3 Exercise sessions as short as 10 min can produce PEH. 2,4,5 This may have important clinical application for exercise prescription, especially for individuals with time constraints that preclude engaging in traditional, longer exercise sessions (for example, 30-40 min). In addition, fractionized exercise may provide a means to capitalize on the benefits of an acute bout of exercise, even if relatively short (for example, p10 min), multiple times per day.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 Consistent with this literature, Park et al 8 previously found that the duration of postexercise hypotension following accumulation of 40 min exercise was associated with the magnitude of change in autonomic function, as assessed by frequency domain measures of heart rate variability. In the present study, they additionally explored the possibility that short-term change in autonomic function might also contribute to blood pressure decrease during rest between exercise bouts.…”
mentioning
confidence: 57%
“…6 Similarly, sedentary adults who already have hypertension have been recommended to resume 30-60 min of continuous or intermittent exercise per day (minimum of 10 min intermittent bouts accumulated throughout the day to a total of 30-60 min) with moderate intensity of 40-70% VO 2 peak. 7 Interestingly, Park et al 8 recently showed in prehypertensive patients that the accumulation of four 10 min walks at 50% VO 2 peak, led to a longer reduction in systolic (11 vs 7 h) and diastolic (10 vs 7 h) blood pressure than did continuous physical activity for 40 min of the same intensity. It is currently unknown whether this hour-long blood pressure-lowering effect of accumulated exercise is a residual of blood pressure decrease during the rest intervals of successive short sessions of exercise.…”
mentioning
confidence: 99%